The Accidental Canon - Patricia G. Berman (Tahiti)
This case study in decanonization examines the making of the exhibition Northern Light: Realism and Symbolism in Scandinavian Painting, 1880–1910 (US and Sweden, 1982–1983). The exhibition became established in the Anglophone world, and internationally, as a framework for understanding Nordic art. It has become a canon that has shaped – and continues to effect – academic and museum practice. The article examines the institutional apparatus and the contingency of circumstances that shaped the contours of the exhibition and thus the canonical model it generated. Among them are the national exigencies in the US (and the five Nordic nations), the scholarly vision of curator Kirk Varnedoe, the exceptional rapidity with which the exhibition was realized, the relatively few Anglophone scholarly sources available in English, and the various pressures placed on the project. The article questions the process of canonization through which an ephemeral exhibition, created for a manifest national purpose in the U.S., generated an enduring art-historical model, even a stereotype. Through a close study of the planning process, the contingent nature of the canon is examined.